Residual Trapping of Supercritical CO2: Direct Pore-scale Observation Using a Low Cost Pressure Cell for Micro Computer Tomography. (July 2017) - Lebedev, Maxim; Zhang, Yihuai; Mikhaltsevitch, Vassili; Inglauer, Stefan; Rahman, Taufiq
Abstract: We describe the design and fabrication steps of a low-cost, modular experimental cell for flooding and X-ray tomography visualization of the rock samples at reservoir conditions (confining pressure up to 45 MPa, pore fluid pressure up to 20 MPa, and temperature up to 80 °C). The main body of the cell is made from Polyether ether ketone (PEEK) tube. The cell can be easily machined and assembled in house from off-the-shelf components at a low cost. Modular design allows adopting the cell to a wide range of X-ray visualization experiments. To demonstrate the capabilities of the equipment we are presenting how the residual CO2 phase spreads in the rock as a function of thermo-physical conditions, namely, for ambient condition CO2 gas, near-critical CO2 gas, liquid CO2, and supercritical CO2 .